1996
DOI: 10.1038/381804a0
|View full text |Cite
|
Sign up to set email alerts
|

A non-enzymatic p21 protein inhibitor of stress-activated protein kinases

Abstract: The stress-activated protein kinases (SAPKs), which are identical to the c-Jun amino-terminal kinases (JNKs), are activated in response to a variety of cellular stresses, including DNA damage, heat shock or tumour-necrosis factor-alpha. SAPK, a subfamily of the mitogen-activated protein (MAP) kinases, is a major protein kinase that phosphorylates c-Jun and other transcription factors. SAPK phosphorylation of transcription factors is important in stress-activated signalling cascades. Here we report that the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
185
3
1

Year Published

1997
1997
2000
2000

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 240 publications
(201 citation statements)
references
References 27 publications
12
185
3
1
Order By: Relevance
“…Speci®cally, this hypothesis has been supported by experiments with undi erentiated and NGF-di erentiated PC12 cells showing that trophic factor withdrawal induced apoptosis could be blocked by dominant-negative ras (Ferrari and Greene, 1994) or various chemical agents capable of inhibiting proliferation (Ferrari et al, 1995;Farinelli and Greene, 1996;Park et al, 1996). In the current study, p21 was clearly able to completely inhibit proliferation of PC12 cells.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…Speci®cally, this hypothesis has been supported by experiments with undi erentiated and NGF-di erentiated PC12 cells showing that trophic factor withdrawal induced apoptosis could be blocked by dominant-negative ras (Ferrari and Greene, 1994) or various chemical agents capable of inhibiting proliferation (Ferrari et al, 1995;Farinelli and Greene, 1996;Park et al, 1996). In the current study, p21 was clearly able to completely inhibit proliferation of PC12 cells.…”
Section: Discussionsupporting
confidence: 71%
“…It should also be noted that p21 has been reported to inhibit the activity of stress-activated protein kinases (SAPKs) JNK1 and p38 (Shim et al, 1996), though inhibition of speci®c processes regulated by SAPKs has not yet been reported. JNK is thought to play a role in death following numerous stimuli, including u.v.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The I 0.5 , ie. the concentration of p21 WAF1/CIP1 required for 50% inhibition of CK2 activity was determined to be 3610 76 M. Shim et al (1996) had found that p21 WAF1/CIP1 acts as a non-enzymatic inhibitor of stress kinases. The observation that p21 WAF1/CIP1 also can act as an inhibitor of CK2 suggests it has several biochemical activities beside the ones originally described (El-Deiry et al, 1993;Harper et al, 1994).…”
Section: Discussionmentioning
confidence: 99%